The association between socioeconomic status and tumour stage at diagnosis of ovarian cancer: A pooled analysis of 18 case-control studies. (April 2016) - Præstegaard, Camilla; Kjaer, Susanne K.; Nielsen, Thor S.S.; Jensen, Signe M.; Webb, Penelope M.; Nagle, Christina M.; Høgdall, Estrid; Risch, Harvey A.; Rossing, Mary Anne; Doherty, Jennifer A.; Wicklund, Kristine G.; Goodman, Marc T.; et al.
Highlights: The association between socioeconomic status (level of education) and tumour stage at diagnosis of ovarian cancer was investigated. Data were obtained from 18 case-control studies that provided individual level measures of level of education. Lower level of education was associated with an increased risk of advanced tumour stage at diagnosis. The results persisted when taking BMI and smoking status into account. The results calls for further studies on how to reduce this diagnostic delay. Abstract: Purpose: Socioeconomic status (SES) is a known predictor of survival for several cancers and it has been suggested that SES differences affecting tumour stage at diagnosis may be the most important explanatory factor for this. However, only a limited number of studies have investigated SES differences in tumour stage at diagnosis of ovarian cancer. In a pooled analysis, we investigated whether SES as represented by level of education is predictive for advanced tumour stage at diagnosis of ovarian cancer, overall and by histotype. The effect of cigarette smoking and body mass index (BMI) on the association was also evaluated. Methods: From 18 case-control studies, we obtained information on 10, 601 women diagnosed with epithelial ovarian cancer. Study specific odds ratios (ORs) with corresponding 95% confidence intervals (CI) were obtained from logistic regression models and combined into a pooled odds ratio (pOR) using a random effects model. Results: Overall, women who completed ≤high school had an increased risk of advanced tumour stage at diagnosis compared with women who completed >high school (pOR 1.15; 95% CI 1.03–1.28). The risk estimates for the different histotypes of ovarian cancer resembled that observed for ovarian cancers combined but did not reach statistical significance. Our results were unchanged when we included BMI and cigarette smoking. Conclusion: Lower level of education was associated with an increased risk of advanced tumour stage at diagnosis of ovarian cancer. The observed socioeconomic difference in stage at diagnosis of ovarian cancer calls for further studies on how to reduce this diagnostic delay.